The progressiveness of Quranic interpretation in the fatwa of Muhammadiyah on female circumcision - Ilham Mundzir; Yulianti Muthmainnah (IAIN Salatiga, 2022)
The Indonesian Muslim community has been accustomed to requesting and carrying out religious Fatwas related to ibadah (worship) or mu’amalah (worldly dealings) in religious organizations that gave rise to various Fatwas, such as Muhammadiyah, Nahdlatul Ulama (NU), and the Indonesian Ulama Council (MUI). This paper focuses on female circumcision, by comparing how the same Quranic verses and Hadith can have various interpretations and Fatwas. Although the source of producing the Fatwa is the same (al-Quran and Hadith), the Fatwa that emerges from three Islamic organization are completely different. Qualitative research methods include interviews and literature review, with Fatwas from religious organizations and interviews being the primary sources. This research concludes that Fatwa from Muhammadiyah is considered the most progressive and has a strong perspective on gender equality and justice by prohibiting female circumcision. On the other hand, the Fatwa from NU and MUI supports and allows female circumcision, even though it has negative impacts on women and baby girls, including the death of baby girls.